2005
DOI: 10.1037/0278-7393.31.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Extrafoveal Objects During Multiple-Object Naming.

Abstract: In 3 experiments, the authors investigated the extent to which objects that are about to be named are processed prior to fixation. Participants named pairs or triplets of objects. One of the objects, initially seen extrafoveally (the interloper), was replaced by a different object (the target) during the saccade toward it. The interloper-target pairs were identical or unrelated objects or visually and conceptually unrelated objects with homophonous names (e.g., animal-baseball bat). The mean latencies and gaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 82 publications
(132 reference statements)
6
75
0
Order By: Relevance
“…However, there is an alternative explanation for these results. It can be hypothesized that the longer fixation durations when a detection occurs are due to the planning and the production of the detection response (Griffin, 2003;Morgan & Meyer, 2005). In other words, Roy-Charland et al's results raise the chicken-and-egg problem: Are the longer fixations responsible for the detections, or are the detections responsible for the longer fixation durations?…”
Section: Methodsmentioning
confidence: 77%
“…However, there is an alternative explanation for these results. It can be hypothesized that the longer fixation durations when a detection occurs are due to the planning and the production of the detection response (Griffin, 2003;Morgan & Meyer, 2005). In other words, Roy-Charland et al's results raise the chicken-and-egg problem: Are the longer fixations responsible for the detections, or are the detections responsible for the longer fixation durations?…”
Section: Methodsmentioning
confidence: 77%
“…This is a technique in which, during the saccade from one object to the next, the object on which the saccade would have landed (the interloper) is replaced by a different object (the target). It has been observed that gaze durations on the target were shorter when the target and the interloper were identical, or each other's mirror image, or associated with the same name than when target and interloper were unrelated Morgan and Meyer, 2005;Schotter et al, 2013). This suggests that speakers processed the interloper prior to fixating on its location.…”
Section: Introductionmentioning
confidence: 85%
“…Given these differences, the easy objects could probably be identified faster than could the Figure 1. Arrangement of objects in Morgan and Meyer (2005;Experiment 2) and in the present study. difficult ones, and their names could be retrieved faster as well (e.g., Brysbaert & Ghyselinck, 2006;Jescheniak & Levelt, 1994;Juhasz, 2005).…”
Section: Materials and Designmentioning
confidence: 95%
“…For the right position, we selected 12 pairs of objects with homophonous names, which had also been used by Morgan and Meyer (2005). Each picture served as a target and as an interloper.…”
Section: Materials and Designmentioning
confidence: 99%
See 1 more Smart Citation